Prevalence and association of mycoplasma infection in the development of coronary artery disease - Yang,J. (2023)
Abstract Coronary heart disease (CHD) has been associated with significant morbidity and mortality worldwide. Although remain controversial, several studies have demonstrated the association of M. pneumoniae infections with atherosclerosis. We evaluated the possible association of mycoplasma infections in patients diagnosed with atherosclerosis by ELISA and PCR methods. Atherosclerotic tissue samples and blood samples were collected for the detection of mycoplasma antibodies (IgA) by ELISA from the 97 patients with coronary artery disease (CAD). M. pneumoniae specific IgA, IgG and IgM were measured by using the Anti-M. pneumoniae IgA/IgG/IgM ELISA. Detection of M. pneumoniae targeting the P1 adhesion gene was performed by PCR Acute infection of M. pneumoniae was diagnosed in 43.3% (42) of patients by PCR. The M. pneumoniae specific antibodies were detected in 36.1% (35) of patients. Twenty-five (25.8%) cases had IgG antibodies, 15 (15.5%) cases had IgM antibodies, 3 (3.1%) cases had IgA antibodies, 10 (10.3%) cases had both IgM + IgG antibodies and 1 (1%) case of each had IgM + IgA and IgG + IgA antibodies. None of the cases was positive for all three antibodies. A Pearson correlation coefficient analysis revealed an excellent correlation between the PCR and the serological results (r=0.921, p<0.001). A majority (17, 40.5%) of the M. pneumoniae positive patients are within the 41-50 years of age group, followed by 10 (23.8%) patients in the age group of 61-70 years and 2 (4.8%) patients were >70 years of age. Our study reported an unusually higher prevalence of M. pneumoniae by serological tests (36.1%) and PCR (43.3%). Although the hypothesis of the association of M. pneumoniae and CAD is yet to be proven, the unusually high prevalence of M. pneumoniae in CAD patients indicates an association, if not, in the development of atherosclerosis.